2007
DOI: 10.19030/jdm.v2i2.5007
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationship Of CEO Nationality With Financial Management, Firm Performance, And CEO Compensation

Abstract: In this exploratory research, and driven by intense interest in media focused

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
(30 reference statements)
3
8
0
Order By: Relevance
“…The international experience (Daily et al 2000) or foreign nationality of the CEO is found to have a significant positive relation with profitability (Sanda et al 2008) and financial performance of the firms (Wah 2015). Also, a study finds that CEOs from Central and South America, Australia and New Zealand earn a higher return on assets than others (Jalbert et al 2007). …”
Section: Ceo Nationality and Firm Performancementioning
confidence: 99%
See 4 more Smart Citations
“…The international experience (Daily et al 2000) or foreign nationality of the CEO is found to have a significant positive relation with profitability (Sanda et al 2008) and financial performance of the firms (Wah 2015). Also, a study finds that CEOs from Central and South America, Australia and New Zealand earn a higher return on assets than others (Jalbert et al 2007). …”
Section: Ceo Nationality and Firm Performancementioning
confidence: 99%
“…The impact of the cultural background of the CEO on firm performance can easily be seen in the differences in compensation of CEOs representing different cultures of the world (Adams et al 2007;Jalbert et al 2007). Upper echelon theory postulates that heterogeneity at the top augments the quality of strategic decisions.…”
Section: Ceo Gender and Firm Performancementioning
confidence: 99%
See 3 more Smart Citations